Pengembangan klon Sukun (Artocarpus altilis (Park.) Fosberg.) unggulan untuk mendukung ketahanan pangan - Hamdan Adma Adinugraha; Dedi Setiadi (Jurnal Biologi Tropika, 2018)
Breadfruit (Artocarpus altilis) is one of multipurpose tree species that their  wood, bark, fruit and leaves can be utilized for human life. The main product of breadfruit is its fruit as one of the potential food sources that has a fairly high nutrient content and is widely consumed as an additional food and even traditional staple foods such as in some countries the Pacific region. The challenge in developing breadfruit as an alternative food source for the community is to prepare the plant material of superior breadfruit clones which have high fruit production and have enough nutrients and chemicals as a source of food and medicinal ingredients. Based on the clones selection at the clonal test plantation in Gunungkidul, Yogyakarta obtained 5 excellent breadfruit populations representing breadfruit cultivars in Indonesia, namely Cilacap, Yogyakarta, Bali island, Bone  and Manokwari. To ensure the availability of seedlings of superior breadfruit clones, the development of planting stocks production techniques is carried out by root cuttings, shoot cuttings and stem cuttings in the nursery that showed better growth succeess (70-100%). Furthermore, information dissemination is carried out to increase efforts to develop breadfruit by the community / user. Breadfruit planting activities are carried out to increase the availability of food reserve forests in the future, both independently and collaboratively with stakeholders  who interested in  developing of breadfruit plantations.